Alternating electron and proton transfer steps in photosynthetic water oxidation - Klauss, André (National Academy of Sciences, 2012)
Water oxidation by cyanobacteria, algae, and plants is pivotal in oxygenic photosynthesis, the process that powers life on Earth, and is the paradigm for engineering solar fuel–production systems. Each complete reaction cycle of photosynthetic water oxidation requires the removal of four electrons and four protons from the catalytic site, a manganese–calcium complex and its protein environment in photosystem II. In time-resolved photothermal beam deflection experiments, we monitored apparent volume changes of the photosystem II protein associated with charge creation by light-induced electron transfer (contraction) and charge-compensating proton relocation (expansion). Two previously invisible proton removal steps were detected, thereby filling two gaps in the basic reaction-cycle model of photosynthetic water oxidation. In the S(2) → S(3) transition of the classical S-state cycle, an intermediate is formed by deprotonation clearly before electron transfer to the oxidant ([Image: see text]). The rate-determining elementary step (τ, approximately 30 µs at 20 °C) in the long-distance proton relocation toward the protein–water interface is characterized by a high activation energy (E(a) = 0.46 ± 0.05 eV) and strong H/D kinetic isotope effect (approximately 6). The characteristics of a proton transfer step during the S(0) → S(1) transition are similar (τ, approximately 100 µs; E(a) = 0.34 ± 0.08 eV; kinetic isotope effect, approximately 3); however, the proton removal from the Mn complex proceeds after electron transfer to [Image: see text]. By discovery of the transient formation of two further intermediate states in the reaction cycle of photosynthetic water oxidation, a temporal sequence of strictly alternating removal of electrons and protons from the catalytic site is established.